1980
DOI: 10.3168/jds.s0022-0302(80)82948-1
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Behavior of Lactating Dairy Cows as Measured by Time-Lapse Photography

Abstract: Evaluation of feeding behavior of ad libitum-fed lactating dairy cows by time-lapse photography revealed 68% of the total feeding activity occurred between the daylight hours of 0600 and 1800. Cows consumed an average of 12.1 meals/day, each 20.9 min in duration. Only 58% of the total defined meal time actually was spent eating, or 253.6 min/cow per day. Estimated meal size and rate of eating, as well as total daily time spent eating, were greater for cows as compared to animals with lower energy demand. Certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 13 publications
4
28
1
Order By: Relevance
“…The number of meals per day observed in the present experiment was similar to the 10.6 meals per day reported by Dado and Allen (1993), and the 10.9 meals reported by Oba and Allen (2000). Others (Vasilatos and Wangsness 1980;Cassida and Stokes 1986) reported a range of 9 to 14 meals d -1 for dairy cows fed TMR diets. It appears that the number of meals per day may be influenced by a variety of factors, including diet composition.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The number of meals per day observed in the present experiment was similar to the 10.6 meals per day reported by Dado and Allen (1993), and the 10.9 meals reported by Oba and Allen (2000). Others (Vasilatos and Wangsness 1980;Cassida and Stokes 1986) reported a range of 9 to 14 meals d -1 for dairy cows fed TMR diets. It appears that the number of meals per day may be influenced by a variety of factors, including diet composition.…”
Section: Discussionsupporting
confidence: 76%
“…7), as shown in previous studies (Heinrichs and Conrad 1987;Gill and Romney 1994;Tolkamp et al 2000). Cows spent more time eating during the afternoon (1500 to 2100) than from midnight to early morning, confirming previous reports for beef cattle (Putnam et al 1964) and dairy cows (Vasilatos and Wangsness 1980;Bermudez et al 1989;Morita et al 1996). Beauchemin (1991) reported that cows spent most of the time eating during daylight hours, and for cows with high intakes, as much as 30% of total intake occurred at night.…”
Section: Daily Eating Patternssupporting
confidence: 77%
See 2 more Smart Citations
“…It has been previously reported that cattle fed in a barn have an average number of 12.1 meals per day (Vasilatos and Wangsness, 1980), or, according to Dado and Allen (1994), around 11 feeding periods per day. Also, an average total feeding time of 253.6 min d −1 (Vasilatos and Wangsness, 1980) or 301.0 min d −1 (Dado and Allen, 1994) was reported for cows held in a barn and fed ad libitum. In this study the individual visits to the feeding trough and the total time spent feeding were recorded automatically by the RIC sys-tem.…”
Section: Discussionmentioning
confidence: 99%